2019
DOI: 10.1038/s41388-019-1035-8
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate restores colorectal cancer chemosensitivity through the p53/miR-149-3p/PDK2-mediated glucose metabolic pathway

Abstract: The development of chemoresistance remains a major challenge that accounts for colorectal cancer (CRC) lethality. Dichloroacetate (DCA) was originally used as a metabolic regulator in the treatment of metabolic diseases; here, DCA was assayed to identify the mechanisms underlying the chemoresistance of CRC. We found that DCA markedly enhanced chemosensitivity of CRC cells to fluorouracil (5-FU), and reduced the colony formation due to high levels of apoptosis. Using the microarray assay, we noted that miR-149-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 59 publications
1
77
1
Order By: Relevance
“…Among them, 3 miRNAs including mmu‐miR‐129‐1‐3p, ‐200b, and ‐149‐3p are conserved between humans and mice. MicroRNA‐200b has been well studied as an epithelial‐mesenchymal transition‐related miRNA and miR‐149‐3p has been reported to be involved in some types of cancers, whereas the role of miR‐129‐1‐3p has not been clearly elucidated. Thus, we focused on miR‐129‐1‐3p.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 3 miRNAs including mmu‐miR‐129‐1‐3p, ‐200b, and ‐149‐3p are conserved between humans and mice. MicroRNA‐200b has been well studied as an epithelial‐mesenchymal transition‐related miRNA and miR‐149‐3p has been reported to be involved in some types of cancers, whereas the role of miR‐129‐1‐3p has not been clearly elucidated. Thus, we focused on miR‐129‐1‐3p.…”
Section: Resultsmentioning
confidence: 99%
“…DCA binds to PDK and attenuates the inhibition of PDH activity, which shifts metabolism from glycolysis to OXPHOS, with subsequent increase of ROS production, decrease of mitochondrial membrane potential, efflux of pro-apoptotic mediators from the mitochondria, and induction of mitochondria-dependent apoptosis [45]. Interestingly, some authors have recently shown that DCA restored colorectal cancer chemosensitivity through the p53/miR-149-3p/PDK2-mediated glucose metabolic pathway [46]. Accordingly, it was also reported that the antitumor activity of DCA was dependent on a functional p53 status, exhibiting synergistic growth inhibitory effects in combination with the p53 activator Nutlin-3 [47].…”
Section: Discussionmentioning
confidence: 99%
“…Upon adding DCA to EGFR TKIs, the inhibition of glycolysis is fatal for the developing tumor. Interestingly, a recently published study shows that DCA also increases the expression of the key tumor suppressor p53 in colorectal cancer, highlighting new possible anticancer mechanisms induced by DCA [95].…”
Section: Discussionmentioning
confidence: 99%